Reformation of Confessional Spiritual Educational Institutions of Ukraine: Containment Factors and Leadership Experience - Kraliuk, Petro (Occasional papers on religion in Eastern Europe, 2020)
The main tendencies, prospects, and complexity of reforming confessional, educational establishments in Ukraine have been systematized and substantiated here. Based on statistics, their quantitative and qualitative characteristics are being examined. Their evolution has been traced from the final years of the Soviet Union to recent days. Currently there are 204 establishments of this kind operating in Ukraine. Due to their large number, they are mostly small. Most of them have dozens of students studying there. Usually, they lack complete and qualified teaching staff and adequate facilities. Orthodox, Catholics, Protestants, Jews, Muslims, and representatives of other denominations get theological education there. The most numerous and well-known are the spiritual, educational institutions belonging to the Orthodox and the Greek Catholic Churches in Ukraine. However, most spiritual, educational institutions have a limited confessional orientation, which leads to a certain isolationism and conservatism in the educational sphere, practicing old confessional models of teaching in theological disciplines. In Ukraine, for a long time, this isolationism has been caused by the reluctance of some state structures to introduce the specialty of "Theology" into educational institutions, allowing its licensing and accreditation. The situation only changed on August 27, 2010, when the Resolution of the Cabinet of Ministers of Ukraine No. 787 allowed doing so. Among the examples of successful reformation of spiritual, educational institutions is the Ukrainian Catholic University, which is a modern, open-type educational institution with a religious orientation. Similar reform tendencies are evident in Saints Cyril and Methodius Uzhhorod Ukrainian Theological Academy, which functions along with Augustine Voloshin Carpathian University, and the Ukrainian Adventist Center for Higher Education. Efforts to reform spiritual education, to modernize it, have recently been observed in the newly created Orthodox Church of Ukraine. The Open Orthodox University of Saint Sophia in Kyiv offers an innovative form of relaying Christian values to the Ukrainian community. It is an extracurricular, interactive platform for learning, spiritual development, and dialogue.